[3 + 2] Cycloaddition reactions of nitrile oxides generated in situ from aldoximes with alkenes and alkynes under ball-milling conditions. Issue 3 (3rd July 2022) - Fang, Run-Kai; Yin, Zheng-Chun; Chen, Jun-Shen; Wang, Guan-Wu
ABSTRACT: A convenient and efficient [3 + 2] cycloaddition reaction of alkenes and alkynes with the in situ generated nitrile oxides from aldoximes in the presence of NaCl, Oxone and Na2 CO3 has been developed to afford a series of isoxazoles and isoxazolines at room temperature in yields up to 85% and 86%, respectively. The current methodology exhibits a wide substrate scope, (hetero)aromatic and aliphatic aldoximes, alkenes including acrylate esters, acrylonitrile, chalcone, styrene, N -methylmaleimide and [60]fullerene, phenylacetylene, and alkynes containing CH2 OH, SiMe3, COCH3 or CO2 CH3 group can be employed. The present protocol features good functional group tolerance, short reaction time, mild reaction conditions and high atom economy, providing an efficient and environmentally friendly access to isoxazoles and isoxazolines. GRAPHICAL ABSTRACT: UF0001